The Fiction View of Models Reloaded. (10th October 2016) - Frigg, Roman; Nguyen, James
Abstract: In this paper we explore the constraints that our preferred account of scientific representation places on the ontology of scientific models. Pace the Direct Representation view associated with Arnon Levy and Adam Toon, we argue that scientific models should be thought of as imagined systems, and clarify the relationship between imagination and representation. 1